Mössbauer spectroscopy with high velocity resolution: New possibilities of chemical analysis in material science and biomedical research - Oshtrakh, M. I.; Semionkin, V. A.; Grokhovsky, V. I.; Milder, O. B.; Novikov, E. G. (Journal of radioanalytical and nuclear chemistry, 2009)
An improvement in velocity resolution of Mössbauer spectroscopy permitted us to carry out a more detailed study of iron chemical state in various iron-containing compounds in a wide range of research. New possibilities of Mössbauer spectroscopy with high velocity resolution were shown in the studies of meteorites, nanocomposites, pharmaceuticals and biological subjects.